Pleomorphic Dermal Sarcoma: a case report - Paula, Carmen Déa Ribeiro de; Abbud, Carolina Bezerra Benévolo; Franceschi, Luiz Eduardo de Almeida Prado; Campos, Aridne Souza Costa; Greggianin, Lucas Frizon; Caldeira, Isadora Ataide; Bastos, Vanessa Queiroz; Esper, Juliana Tomaz (Brazilian Journal of Case Reports, 2023)
This case report brings a 79-year-old man, with a history of melanoma in situ on the extensor part of the left arm, who presented with an ulcerated nodule on the scalp, right parietal region, with rapid and progressive growth for 3 months. The lesion was clinically compatible with squamous cell carcinoma, Merkel carcinoma, amelanotic melanoma and pleomorphic dermal sarcoma. Exeresis was performed and the diagnosis of Pleomorphic Dermal Sarcoma (PDS) was confirmed by histological and immunohistochemical evaluation. Pleomorphic Dermal Sarcoma (PDS), formerly known as malignant fibrous histiocytoma or undifferentiated pleomorphic sarcoma of the skin, is a rare spindle cell mesenchymal tumor that may recur locally or metastasize. Our objective is to present this rare tumor to the reader, discussing the clinical, histological and immunohistochemical presentation, and to highlight the need for further studies on surgical management protocols and the development of guidelines for the standardization of management and safe follow-up of these patients.